2021
DOI: 10.3390/cancers13030571
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Secretome Is Altered in Rectal Cancer Tissue Compared to Normal Rectal Tissue, and Alterations in the Secretome Induce Enhanced Innate Immune Responses

Abstract: Locally advanced rectal cancer is treated with neoadjuvant-chemoradiotherapy; however, only ~22% of patients achieve a complete response, and resistance mechanisms are poorly understood. The role of inflammation and immune cell biology in this setting is under-investigated. In this study, we profiled the inflammatory protein secretome of normal (non-cancer) (n = 8) and malignant rectal tissue (n = 12) pre- and post-radiation in human ex vivo explant models and examined the influence of these untreated and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
2
10
0
Order By: Relevance
“…Rectal cancer response to NACRT has been unanimously considered an important prognostic factor for this disease, that is why current research (32, 33) is focusing on predicting patients that would have an increased benefit from this therapeutic approach. Rectal cancer tissue is highly inflammatory, and the levels of inflammatory markers may correlate with obesity status (34). Although our study reported higher relapse rates for DM rectal cancer patients, we should also consider that DM oncological patients suffering that undergo surgery following NACRT usually have higher rates of surgical complications, especially wound infection, and need more treatment recovery time (35).…”
Section: Discussionmentioning
confidence: 61%
“…Rectal cancer response to NACRT has been unanimously considered an important prognostic factor for this disease, that is why current research (32, 33) is focusing on predicting patients that would have an increased benefit from this therapeutic approach. Rectal cancer tissue is highly inflammatory, and the levels of inflammatory markers may correlate with obesity status (34). Although our study reported higher relapse rates for DM rectal cancer patients, we should also consider that DM oncological patients suffering that undergo surgery following NACRT usually have higher rates of surgical complications, especially wound infection, and need more treatment recovery time (35).…”
Section: Discussionmentioning
confidence: 61%
“…[ [46][47][48][49][50][51][52][53][54]. Extracellular vesicles (EVs) are secreted lipid-encapsulated vesicles representing an active element of the cell secretome [55].…”
Section: Significance Statementmentioning
confidence: 99%
“…This complex mixture of proteins, lipids and nucleic acids allows for the regulation of a broad range of cellular behaviors and physiological functions. Changes in the abundance of components of the secretome are observed in many diseases, including cancer and actively shape the TME to contribute to tumor progression [46–54]. Extracellular vesicles (EVs) are secreted lipid‐encapsulated vesicles representing an active element of the cell secretome [55].…”
Section: Introductionmentioning
confidence: 99%
“…CCL22 is a chemokine that modulates immunity by increasing Treg contact with dendritic cells in lymph nodes through CCR4 receptor signaling ( 47 , 48 ). In melanoma, CCL22 boosts Treg recruitment into the TME while inhibiting anticancer immunity ( 49 ) and in colorectal adenocarcinomas, CCL22 mRNA expression is considerably higher in tumor tissue than in corresponding normal tissue ( 50 ). CCL22 is also associated with Treg and Th1 cells in CRC patients who were exposed to gut microbiota.…”
Section: Discussionmentioning
confidence: 99%